Justification of Scanning Contact Potentiometry Applicability to Test NPP Equipment during its Manufacture - Vitaly I Surin; Alexander S Shcherban; Alexander A Shcherbakov; Maxim E Zhidkov; Sergey A Tomilin; Mikhail B Ivanyi (Глобальная ядерная безопасность)
The method of scanning contact potentiometry (SCP) was investigated in factory conditions and functional capabilities of electric non-destructive testing (NDT) method to detect structural heterogeneities and technological defects were demonstrated directly in the process of reactor equipment production.